2020
DOI: 10.1186/s13071-020-04387-6
|View full text |Cite
|
Sign up to set email alerts
|

Point prevalence mapping reveals hotspot for onchocerciasis transmission in the Ndikinimeki Health District, Centre Region, Cameroon

Abstract: Background Ivermectin-based preventive chemotherapy (PC) is distributed annually to all at-risk populations eligible for ivermectin treatment to control and/or eliminate onchocerciasis. Information on the impact of mass ivermectin administration on onchocerciasis transmission is scanty, and it is tricky to appreciate the progress towards elimination and engage corrective measures. To fill that gap in the Centre Region in Cameroon, the current onchocerciasis endemicity level in the Ndikinimeki Health District a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Two longitudinal studies asked respondents to recall their previous treatment behaviour at each round, over six annual rounds in Ethiopia for trachoma (34), and over 10 annual rounds in Nigeria for onchocerciasis (35). Three cross-sectional studies asked participants to recall their treatment behaviour during MDA for onchocerciasis over a specific time period, either five annual rounds (40) and 11+ annual rounds (36) in Cameroon, or 10 biannual rounds in Ethiopia (42). Two of these studies referred to compliance in line with the definitions considered for this review (40, 42).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two longitudinal studies asked respondents to recall their previous treatment behaviour at each round, over six annual rounds in Ethiopia for trachoma (34), and over 10 annual rounds in Nigeria for onchocerciasis (35). Three cross-sectional studies asked participants to recall their treatment behaviour during MDA for onchocerciasis over a specific time period, either five annual rounds (40) and 11+ annual rounds (36) in Cameroon, or 10 biannual rounds in Ethiopia (42). Two of these studies referred to compliance in line with the definitions considered for this review (40, 42).…”
Section: Resultsmentioning
confidence: 99%
“…Three cross-sectional studies asked participants to recall their treatment behaviour during MDA for onchocerciasis over a specific time period, either five annual rounds (40) and 11+ annual rounds (36) in Cameroon, or 10 biannual rounds in Ethiopia (42). Two of these studies referred to compliance in line with the definitions considered for this review (40, 42). A further two cross-sectional studies asked participants to recall ever being treated during MDA for lymphatic filariasis in Ghana (37, 38).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of the geographic distribution of onchocerciasis in Cameroon revealed that onchocerciasis is endemic in all the ten regions of Cameroon with approximately 60% of the population living in high-risk areas for the disease [ 31 ]. Furthermore, assessment of communities which have been receiving preventive chemotherapy for close to 20 years revealed the continuous spread of the parasite in some communities [ 51 , 52 ]. The OvMCBL02 test is an antibody-based test which is unable to differentiate between past and current infection; thus, control samples were obtained from Rwanda and Europe rather than Cameroon to exclude the possibility of including healthy individuals that may have been infected with the parasite in the past.…”
Section: Discussionmentioning
confidence: 99%
“…20 In conclusion, the findings from various of the African continent is fragmented, not informative and a wide range of prevalence of onchocerciasis infection: they were reported ranging from 6.32% to 17% in Ethiopia. [21][22][23] 2.43% to 13.2 in Ghana, 24 1.7% to 23.7% in Uganda, 25 7% to 19% in Cameron, [26][27][28] 5% to 73% in Côte d'Ivoire and Burkina Faso, 29 49% to 83.2% in Tanzania. 30 Therefore, understanding the pooled prevalence of onchocerciasis infection is paramount to design sound preventive and control strategies targeted to eliminate and eradicate the newly appearing infection in the region.…”
Section: Introductionmentioning
confidence: 99%